Marketing Strategy for "Anchovies Pizza" Processed Product in Munjungagung Village, Tegal Regency - Nurwildani, Mohammad Fajar; Hidayat, Tofik; Zulfah, Zulfah (ASEAN Journal of Empowering Community, 2024)
Munjungagung Village is one of the villages bordering the northern coast of Java. Being located in a coastal area makes Munjungagung Village rich in marine fishery resource potential. The potential fishery resources are mostly generated by capture fisheries. In addition to fishery and marine resource potential, Munjungagung Village also has potential for marine tourism and a conservation area in the Jeruk Reef region. To support the fishery and marine sectors, Munjungagung Village has fishery infrastructure in the form of the PPP Larangan coastal fishery port, the PPI Larangan fish landing base, and the TPI Larangan fish auction site. As an area bordering the coastal region, Munjungagung Village also has a marine tourism attraction, namely the Larangan Beach. The catch of fish by the fishermen is very abundant, including anchovies. Anchovies are one of the quite potential fishery products in Munjungagung Village, Kramat District, Tegal Regency. However, in its utilization, fishermen only sell anchovies in wet form. Through community empowerment activities, mothers can diversify processed anchovy products by making a pizza called "Anchovies Pizza." One of the strategies that can be implemented in empowering the coastal community of Munjungagung Village is through the optimization of fishery products based on anchovies. Anchovy products can be optimized, one of which is by making "Anchovies Pizza." Through an economic-based approach for the coastal community, especially among mothers, it is hoped that the economic status of the coastal community can be improved.